Assessing knowledge about acupuncture: A survey of people with back pain in the UK. (December 2016) - Greville-Harris, Maddy; Hughes, John; Lewith, George; Liossi, Christina; White, Peter; Graham, Cynthia A.; Bishop, Felicity L.
Highlights: 202 adults with back pain completed a survey assessing knowledge of acupuncture. More than 80% correctly answered questions on efficacy, side-effects, and styles. Fewer people knew about public sector provision, regulation, or electro-acupuncture. Addressing these knowledge gaps would improve public awareness of acupuncture. Abstract: Objectives: Despite the prevalence of acupuncture treatment in the UK, and the increasing evidence of safety and effectiveness, the information presented to patients by practitioners frequently contains inaccuracies. As knowledge of treatment affects both patient decision-making and treatment outcomes, this study aimed to establish what is known about acupuncture in a sample of people who had, and had not, previously experienced acupuncture. Design: A 15-item questionnaire was constructed to assess knowledge of acupuncture. Setting: Online survey of people with a history of back pain. Results: 202 participants completed the questionnaire. 66.8% of the sample was female and 33.2% male, with a mean age of 35 years (range 18–74 years). 87.6% had back pain in the past six months, 44.1% currently. 21.8% had previously received acupuncture, and 69.8% had previously read or heard information about acupuncture. On average participants answered 11.03 of 15 questions about acupuncture correctly (SD = 2.64). Items relating to common concerns about acupuncture, acupuncture efficacy, and types of acupuncture were correctly answered by ≥80% of participants. Participants possessed less knowledge of accessibility, Government legislation, and methods of administration. Conclusions: The study identified key gaps in knowledge about acupuncture among patients. In particular, many participants were unaware that acupuncture is available from the UK National Health Service and that acupuncturists are not subject to statutory regulation in the UK. These knowledge gaps should be addressed in order to increase people's understanding of and access to acupuncture.